2011
DOI: 10.1111/j.1601-183x.2011.00678.x
|View full text |Cite
|
Sign up to set email alerts
|

ImprintedRasgrf1expression in neonatal mice affects olfactory learning and memory

Abstract: Rasgrf1 is genomically imprinted; only the paternally inherited allele is expressed in the neonatal mouse brain until weaning, at which time expression becomes biallelic. Whereas Rasgrf1 has been implicated in learning and memory via knockout studies in adult mice, the effect of its normal imprinted expression on these phenotypes has not yet been examined. Neonatal mice with experimentally manipulated patterns of imprinted Rasgrf1 expression were assessed on an associative olfactory task. Neonates lacking the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Though previous work has shown that infant mice display preferences for maternal and homecage odors (Logan et al 2012; Thomas et al 2010) and are able to form conditioned memories (Akers et al 2012; Alleva & Calamandrei 1986; Bollen et al 2012; Bouslama et al 2005; Drake et al 2011; Durand et al 2003; Nagy et al 1972; Wiedenmayer et al 2000), to our knowledge, our data here are the first to show preference learning in infant mice despite an aversive conditioning paradigm, and thus are first to illustrate a sensitive period for attachment-based learning. Similar to developing rats, infant mice display a stress hyporesponsive period (Cirulli et al 1994; D’Amato et al 1992; Schmidt et al 2003).…”
Section: Discussionmentioning
confidence: 48%
“…Though previous work has shown that infant mice display preferences for maternal and homecage odors (Logan et al 2012; Thomas et al 2010) and are able to form conditioned memories (Akers et al 2012; Alleva & Calamandrei 1986; Bollen et al 2012; Bouslama et al 2005; Drake et al 2011; Durand et al 2003; Nagy et al 1972; Wiedenmayer et al 2000), to our knowledge, our data here are the first to show preference learning in infant mice despite an aversive conditioning paradigm, and thus are first to illustrate a sensitive period for attachment-based learning. Similar to developing rats, infant mice display a stress hyporesponsive period (Cirulli et al 1994; D’Amato et al 1992; Schmidt et al 2003).…”
Section: Discussionmentioning
confidence: 48%
“…The reason behind using 1000 bp up- and downstream was that tandem repeats associated with ICRs are either found within or adjacent to the ICRs (Thorvaldsen et al, 1998; Okamura et al, 2000; Takada et al, 2002). The repeats associated with Rasgrf1 in mice are found within the ICR (Brideau et al, 2010). …”
Section: Methodsmentioning
confidence: 99%
“…Qki (KH domain containing RNA binding) is a RNA-binding protein that influences glial cell fate and development (Hardy, 1998), but also plays an essential role in myelinisation processes, since spontaneous mutations in this protein result in hypomyelinization of the central and peripheral nervous systems (Hardy et al, 1996, Lu et al, 2003, Larocque and Richard, 2005. Rasgrf1 (Ras protein-specific gunine nucleotidereleasing factor1) is a guanine nucleotide exchange factor (GEF) that promotes dissociation of GDP from RAS protein in the brain in response to Ca 2+ influx, muscarinic receptor signalling, or activation of the G protein beta-gamma subunit, and appears crucial for long-term memory formation in mouse model systems (Drake et al, 2011, Barman et al, 2014, Manyes et al, 2018. Atxn10 (Ataxin 10) is a cytoplasmic protein required for neuron survival, differentiation and neuritogenesis via activation of mitogen-activated protein kinase cascade (Marz et al, 2004, Waragai et al, 2006.…”
Section: Ndrg4 Qki Rasgrf1 Atxn10 and Nedd4 Are Highly Dynamic Promentioning
confidence: 99%